2022
DOI: 10.1111/jocs.16312
|View full text |Cite
|
Sign up to set email alerts
|

Variable definitions and treatment approaches for atrial functional mitral regurgitation: A scoping review of the literature

Abstract: Objectives Atrial functional mitral regurgitation (AFMR) is a subtype of functional mitral regurgitation due to longstanding atrial fibrillation (AF) or heart failure with preserved ejection fraction. The variation in AFMR' definition and the common mode of treatment described in the literature remain unknown. Methods We performed a scoping review of studies that surgically treated AFMR to characterize the existing variability in the definition of AFMR, the type of operations performed for AFMR valvulopathy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Recent evidence suggests that the prognosis of MR patients undergoing surgery is different between those with AFMR and VFMR, suggesting that distinguishing the two functional MRs for surgical candidates may have long‐lasting therapeutic implications. Two retrospective studies have found that mitral valve annuloplasty, the preferred surgical strategy to treat AFMR, 36 yielded better clinical outcomes, including long‐term survival in AFMR compared to VFMR 33,37 . While our study did not find any significant differences between AFMR and VFMR with TEER, our long‐term outcome for MR ≤ 2 of 97.1% was comparable to 93%–94% in mitral valve annuloplasty; thus, TEER may be a viable less invasive option for patients who are ineligible for surgery 33,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the prognosis of MR patients undergoing surgery is different between those with AFMR and VFMR, suggesting that distinguishing the two functional MRs for surgical candidates may have long‐lasting therapeutic implications. Two retrospective studies have found that mitral valve annuloplasty, the preferred surgical strategy to treat AFMR, 36 yielded better clinical outcomes, including long‐term survival in AFMR compared to VFMR 33,37 . While our study did not find any significant differences between AFMR and VFMR with TEER, our long‐term outcome for MR ≤ 2 of 97.1% was comparable to 93%–94% in mitral valve annuloplasty; thus, TEER may be a viable less invasive option for patients who are ineligible for surgery 33,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular dysfunction was defined as those with LVEF <55% regardless of atrial dimension or atrial arrhythmia histories. We adopted this definition while recognizing that prior studies have variably defined atrial dysfunction [ 16 ]. LVEF was estimated using 2D or 3D volumetric tracing.…”
Section: Methodsmentioning
confidence: 99%
“… 88 Mitral valve surgery typically entails restricted ring annuloplasty. 89 A large annular area may impede coaptation unless the ring is significantly undersized. This, however, raises the likelihood of dehiscence and mitral stenosis.…”
Section: Treatment Of Afmrmentioning
confidence: 99%